Association between physical activity and subjective memory decline triggered by the COVID-19 pandemic: Findings from the PAMPA cohort - Feter, Natan (Prev Med, 2021)
Implementation of social distancing reduced the incidence of coronavirus disease (COVID-19) cases. Nevertheless, this strategy has other undesirable effects such as physical inactivity and psychological distress, which are associated with cognitive impairment. We aimed to examine whether physical activity during social distancing restrictions could reduce the risk of subjective memory decline in adults. Participants (n=2321) completed the baseline assessment of PAMPA cohort (Prospective Study About Mental and Physical Health), a ambispective cohort study conducted in southern Brazil. An online-based, self-administered questionnaire assessed physical activity and self-rated memory in two different periods: before and during social distancing. Data collection was executed from June 22nd to July 23rd 2020. Adjusted Poisson regression models were performed and values reported in prevalence ratio (PR) with 95% confidence interval (CI). Participants presented with a mean age of 38.2 (95%CI: 37.5, 38.9) years. Most were women (76.6%), had at least a university degree (66.7%), and were overweight or obese (53.3%). Subjective memory decline was reported by 30.0% (95%CI: 27.7%, 32.4%) of respondents. Most individuals with subjective memory decline reported being physically inactive during the pandemic of COVID-19. Participants were less likely to experience subjective memory decline if they either became (PR: 0.56; 95%CI: 0.36, 0.89) or remained (PR: 0.68; 95%CI: 0.49, 0.93) physically active compared to inactive respondents. Physical activity participation during social distancing reduced the likelihood of subjective memory decline in adults. Physical activity should be highlighted as a potential alternative to reduce the burden of the COVID-19 pandemic on cognitive function and mental health.